Analysis method of isolation layer composed of high damping rubber bearings based on deformation history integral type model. (1st February 2022) - Zhou, Zhiguang; Li, Yiwen; Hu, Xiaorong
Highlights: The equivalent linearization parameter formulas of isolation layer composed of HDRBs based on the deformation history integral type model are derived. An iterative procedure to calculate the maximum deformation of isolation layer is established. Comparison of NLTH analysis and EL method is realized through case study to verify the validity of the new proposed method. The new proposed method is practical in design of isolation layer composed of HDRBs. Abstract: As the high damping rubber bearings (HDRBs) presents stronger nonlinear material effects, the deformation history integral type model (DHI model) validated to well simulate the mechanical behaviors was adopted instead of traditional bilinear model. While considering the computational cost of the nonlinear time history (NLTH) analyses, simplified analysis methods represented by the equivalent linearization (EL) method has been widely applied to estimate the structural response, especially in the cases where isolated structures can be simplified to single-degree-of-freedom systems. The EL parameter calculation formulas based on the DHI model was derived to realize the equivalent linearization analysis of isolation layer composed of HDRBs, and the formulas were applied to an iterative process for calculating the maximum deformation of the isolation layer. A six-story isolated building was taken as an example to verify the accuracy of the proposed method. It was shown that the estimated results of the iterative approach have limited difference with the structure responses obtained from NLTH analyses. Therefore, the established model can be further applied for the assessment of the seismic demands of structures isolated by HDRBs.